Fiqh Model of the Companions (Saḥābah) of the Prophet and its Influence on Abu Hanifah's Rational Fiqh and Malik's Traditional Fiqh - Achmad Kholiq; Achyar Zein (AHKAM : Jurnal Ilmu Syariah, 2021)
This study examines the influence of the ijtihād methods of the Prophet’s companion on two major schools of thought in Islamic legal tradition. These are the rational thinking of Abu Hanifah, known as ahl al-ra’y, and Malik ibn Anas, known as ahl al-hadīth. This study is a historical enquiry by critically analyzing significant events in the past around the lives of those two figures. Various historical resources are used, tārikh tashrī’ and fiqh (Islamic jurisprudence) literature, etc. This study finds out that there is a positive influence of the Prophet’s companions’ ijtihād methods with the legal thinking of Abu Hanifah and Malik ibn Anas. This implies that the method significantly influences the formulation of Islamic jurisprudence by those two figures.  Abstrak:Penelitian ini mengkaji pengaruh metode ijtihad para sahabat nabi terhadap dua mazhab besar dalam tradisi hukum Islam. Metode tersebut yakni  pemikiran rasional Abu Hanifah yang dikenal dengan ahl al-ra'y dan Malik bin Anas yang dikenal dengan ahl al-hadits. Kajian ini merupakan penyelidikan sejarah dengan menganalisis secara kritis peristiwa-peristiwa penting di masa lalu seputar kehidupan kedua tokoh tersebut. Untuk itu,  digunakan berbagai  sumber sejarah, literatur tarikh tashri’ dan kitab fikih, dll. Penelitian ini menemukan bahwa ada pengaruh positif metode ijtihad para sahabat nabi dengan pemikiran hukum Abu Hanifah dan Malik ibn Anas. Hal ini menunjukkan bahwa metode berpengaruh secara signifikan terhadap perumusan fikih Islam oleh kedua tokoh tersebut.